L’oléiculture en France : quand le paysage participe au renouveau d’une activité agricole - Stéphane Angles; Étienne Grésillon; Paul Minvielle (Projets de Paysage)
After a long decline, olive growing in France has experienced a marked revival since the 1980s thanks to the valorization of local olive products. The great variety of profiles of the stakeholders in this re-emergence of olive production, especially among amateur olive growers, contributes greatly to the generation of the new olive growing landscapes. These landscapes are a major outcome of the rebirth of olive growing, a phenomenon worthy of research. The dynamics at work in the olive-producing landscape are varied and highlight the high value of the different types of landscapes introducing more environmentally friendly practices and providing an increasingly appreciated regional heritage. They thus contribute to the versatility of local farming areas and make it possible to understand the profound changes affecting the French Mediterranean region.